Enzymatic activity pattern in peanut seeds at different periods of artificial aging - de Moraes, Amanda C. P. [UNESP]; Barbosa, Rafael M.; Unêda-Trevisoli, Sandra H. [UNESP]; Vieira, Bruno G. T. L. [UNESP]; Vieira, Roberval D. [UNESP] (My University, 2016)
The study of enzymes involved in the deterioration of peanut seeds during storage has been important in the detection of early stages of this process. This study was aimed at standardizing a protein extraction protocol and evaluate its suitability for peanut (Arachis hypogaea L.) seeds aged for various times. We examined the hypocotyl-radicle axes of peanut seeds variety Runner IAC 886 harvested in 2007-2008 and 2011-2012 pre-sprouted and stored in a climate chamber at 25°C. Seeds were subjected to different treatments followed by artificial aging, and evaluated at the time intervals of 0, 6, 12, 24, 36, 48, 60, 72, 96, and 120 hours. Seeds were then analyzed by vertical electrophoresis using 5% (stacking) and 10% (separating) polyacrylamide gels performed at 4°C, with normal and constant polarity of 25 mA at 200 V. Detection systems were used for the following enzymes: esterase, malate dehydrogenase, glutamate dehydrogenase, and superoxide dismutase. The extraction buffer consisted of 0.025 M Tris pH 8.3 + 0.019 M glycine + 0.001 EDTA produced the most distinct bands in seeds from the two harvests in all enzymatic systems. In the artificial aging treatment, the activity of esterase decreased after 48 h, while that of glutamate dehydrogenase increased after 96 h, and those of malate dehydrogenase and superoxide dismutase remained unaltered.
Keywords: Arachis hypogaea L.; Enzyme; Seed deterioration; Vigor of seeds